A calculation of the physical mass of sigma meson - Morones Ibarra, José Rubén; Santos Guevara, Ayax (Indian Academy of Sciences, 2007)
We calculate the physical mass and the width of the sigma meson by considering that it couples in vacuum to two virtual pions. The mass is calculated by using the spectral function, and we find that it is about 600 MeV. In addition, we obtained 220 MeV as the value for the width of its spectral function. The value obtained for the mass is in good agreement with that reported in the Particle Data Book for the σ-meson, which is also named f0(600). This result also shows that σ-meson can be considered as a two-pion resonance